Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Labile and stable organic carbon in soils of cacao agroforestry systems compared to forest and pasture in the Colombian Amazon - Juan Carlos Suárez; Cesar Julian Lopez; Wilson Rodriguez (Agroforestry Systems, 2026)
The study analyzed labile and stable SOC fractions in different land use systems in the Colombian Amazon. The research included cacao-based Agroforestry Systems (cAFS), full-sun cocoa plantations, forests, and pastures, using a factorial design with land use and soil depth as factors. Land use significantly affected carbon fractions, explaining 51% of variance ( P −1 ) and lowest in Pasture (2.76 g C kg −1 ). For humic acids, full-sun cacao showed the highest values (9.55 g C kg −1 ) followed by Capiron (7.75 g C kg −1 ). Total Humic Extract was maximum in full-sun cacao (27.68 g C kg −1 ) and minimum in Pasture (18.99 g C kg −1 ). The polymerization index was higher in Pasture (1.87) and full-sun cacao (1.46). The degree of humification was highest in full-sun cacao (64.78%), while the humification ratio showed maximum values in full-sun cacao (84.9%) and minimum in Forest (36.86%). These patterns generally persisted at deeper soil layers, demonstrating the potential of cAFS as a sustainable alternative for land use and carbon sequestration.

Late Quaternary evolution of a large rock slope deformation (Robinson, English Lake District) – a first such exploration by cosmogenic exposure dating in the British mountains - Peter Wilson; David Jarman; Maria Miguens-Rodriguez; Derek Fabel (Proceedings of the Geologists' Association, 2025)

Host‐Microbiome Associations in Livebearing Fishes Adapted to Toxic Environments Rich in Hydrogen Sulfide - Elizabeth J. Wilson; Sonny T. M. Lee; Lydia H. Zeglin; Lenin Arias Rodriguez; Michael Tobler (Molecular Ecology, 2025)
Organisms inhabiting extreme environments must tolerate a variety of physiochemical stressors. In some cases, host‐associated microbial communities facilitate the survival of their hosts in extreme environments, but extremophile symbioses have not been identified in vertebrates. We used 16S rRNA amplicon sequencing to investigate commonalities and differences in the gut bacterial communities of livebearing fishes ( Poecilia mexicana species complex, Poeciliidae) that have repeatedly colonised toxic sulfide streams in southern Mexico. We found shared gut microbial taxa across habitat types and drainages but also differences in the microbiomes between sulfidic and nonsulfidic populations, both in terms of patterns of diversity and community composition. Most importantly, we documented convergent changes in microbiome composition across evolutionarily independent sulfide spring lineages. These patterns were consistent when we analysed the gut microbiomes as well as primarily host‐associated microbiomes that excluded taxa that are commonly found in the environment. Our analyses also revealed several microbial taxa associated with sulfide spring coloniation that have previously been implicated in symbioses and may influence the host's tolerance to the extreme environmental conditions. Our study sheds light on how shared environmental pressures can give rise to convergent host‐microbiome associations in fishes, and it provides a foundation for investigating the role of host‐microbiome interactions in vertebrate adaptation to extreme environments.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Contrast enhancement after mechanical thrombectomy: clinical correlations and impact on outcomes - Farid Khasiyev; Wilson Rodriguez; Gunjanpreet Kaur; Irshad Allahverdiyev; Brian Miremadi; Kara Christopher; Guillermo Linares (Acta Neurologica Belgica, 2025)

Bacterial dynamics and volatile metabolome changes of vacuum-packaged beef with different pH during chilled storage - Magdevis Y. Rodriguez-Caturla; Larissa P. Margalho; Juliana S. Graça; Arthur K.R. Pia; Viny L. Xavier; Melline F. Noronha; Lucélia Cabral; Wilson J.F. Lemos-Junior; Carmen J.C. Castillo; Anderson S. SantˈAna (International Journal of Food Microbiology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Transcriptomic and developmental effects of persistent organic pollutants in sentinel fishes collected near an arctic formerly used defense site - Renee Jordan-Ward; Frank A. von Hippel; Maria Eugenia Sancho Santos; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Tom Titus; Alison Gardell; Amina Salamova; John H. Postlethwait; Elise Contreras; Staci L. Capozzi; et al. (Environmental Pollution, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Differential gene expression and developmental pathologies associated with persistent organic pollutants in sentinel fish in Troutman Lake, Sivuqaq, Alaska - Renee Jordan-Ward; Frank A. von Hippel; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Elise Contreras; Alison Gardell; Michael R. Minicozzi; Tom Titus; Bobby Ungwiluk; Pamela Miller; David Carpenter; et al. (Environmental Pollution, 2024)

Long-range transport and microscopy analysis of Sangay volcanic ashes in Ecuador - Daniel Moran-Zuloaga; Wilson Merchan-Merchan; Emilio Rodriguez-Caballero; Maurizio Mulas; Philip Hernick (Air Quality, Atmosphere & Health, 2024)
This study aims to conduct a spatiotemporal analysis of the long-range transportation of volcanic ashes that originates from the eruption of the Sangay volcano and reached Guayaquil during the months of June 2020; September 2020; and April 2021. The particulate matter data (PM 2.5 ) was obtained using a low-cost air quality sensor. During the wet season of 2020 (Jan–May), PM 2.5 average concentrations were 6 ± 2 μg m −3 while during the dry season of 2020 (July–Nov), PM 2.5 average concentrations were 16 ± 3 μg m −3 in Guayaquil. The most prominent plumes occurred on September 20th of 2020, a month with no rain but high wind speeds created by the Andes Mountain topography to the coast. During this event, PM 2.5 concentrations started at 12:00 UTC-5 in a volcanic plume event that lasted 4 h with a maximum peak of 133 + 40 μg m −3 . Electron microscopy of selected samples showed that the ashes of the three eruptions may differ in size and morphology. EDX analysis reveals that the ash contains certain elements—C, Si, Na, Mg, Al, Ca, S, and Fe—in similar proportions. In summary, this study remarks on the meteorological role and the long-range transport of Sangay volcanic ashes.

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Cosmogenic (10Be) surface-exposure ages from the Burtness Comb rock avalanche, Lake District, northwest England - Peter Wilson; David Jarman; Maria Miguens-Rodriguez; Derek Fabel (Proceedings of the Geologists' Association, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Probabilistic approximation to change and no change in multispectral remote sensing - Victor Hugo Gutierrez-Velez; Jeronimo Rodriguez-Escobar; Wilson Lara; Victoria Sarmiento-Giraldo (International Journal of Remote Sensing, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Methylene blue modulates functional connectivity in the human brain - Pavel Rodriguez; Amar P. Singh; Kristen E. Malloy; Wei Zhou; Douglas W. Barrett; Crystal G. Franklin; Wilson B. Altmeyer; Juan E. Gutierrez; Jinqi Li; Betty L. Heyl; Jack L. Lancaster; F. Gonzalez-Lima; et al. (Brain Imaging and Behavior, 2017)

Identification of a Novel Moth Sex Pheromone Component from Chilecomadia valdiviana - Heidy Herrera; Wilson Barros-Parada; M. Fernanda Flores; Wittko Francke; Eduardo Fuentes-Contreras; Marcela Rodriguez; Francisca Santis; Paulo H. G. Zarbin; Jan Bergmann (Journal of Chemical Ecology, 2016)

Social network analysis resolves temporal dynamics of male dominance relationships - David Bierbach; Sophie Oster; Jonas Jourdan; Lenin Arias-Rodriguez; Jens Krause; Alexander D. M. Wilson; Martin Plath (Behavioral Ecology and Sociobiology, 2014)

Opacification of Shape Memory Polymer Foam Designed for Treatment of Intracranial Aneurysms - Jennifer N. Rodriguez; Ya-Jen Yu; Matthew W. Miller; Thomas S. Wilson; Jonathan Hartman; Fred J. Clubb; Brandon Gentry; Duncan J. Maitland (Annals of Biomedical Engineering, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)